2002
DOI: 10.1038/sj.bmt.1703629
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphism associates with graft-versus-host disease and survival in HLA-matched sibling allogeneic bone marrow transplantation

Abstract: Summary:We investigated the role of polymorphism of the vitamin D receptor (VDR) gene in HLA-matched sibling BMT for polymorphisms previously associated with human disease pathology. In intron 8 of the VDR gene, the B and A alleles of the BsmI and ApaI RFLPs were found to associate with reduced aGVHD when present in the patient's genotype. Logistic regression analysis demonstrated that patient VDR genotype, along with previously identified IL-10 ؊1064 and IFN-␥ genotype to be risk factors for severe acute GVHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 21 publications
5
54
0
2
Order By: Relevance
“…Accordingly, it has been shown that vitamin D analogs prevent acute GvHD in rat BMT and that the VDR gene polymorphism associates with GvHD and survival. 4,5 Up to now, no data are available on the endogenous serum levels of vitamin D metabolites during the course of BMT. In this study we measured 25-hydroxyvitamin D 3 (25(OH)D 3 ) and 1,25(OH) 2 D 3 in consecutive serum samples of 48 patients before and after allogeneic BMT.…”
mentioning
confidence: 99%
“…Accordingly, it has been shown that vitamin D analogs prevent acute GvHD in rat BMT and that the VDR gene polymorphism associates with GvHD and survival. 4,5 Up to now, no data are available on the endogenous serum levels of vitamin D metabolites during the course of BMT. In this study we measured 25-hydroxyvitamin D 3 (25(OH)D 3 ) and 1,25(OH) 2 D 3 in consecutive serum samples of 48 patients before and after allogeneic BMT.…”
mentioning
confidence: 99%
“…6,7 Previous reports describe the efficacy of a vit D analog MC1288 in preventing acute GVHD in a rat BM transplant model, 8 as well as the relationship between vit D receptor gene polymorphism, and acute and cGVHD. 9 The effects of vit D are mediated by the nuclear vit-D receptor. It is constitutively expressed in monocytes, and in both B-and T-activated lymphocytes.…”
mentioning
confidence: 99%
“…24 A study in 2003 showed that IL10-592A/A compared with C/C genotype was associated with acute GVHD. 25 In 2002, Middleton and associates 26 examined the association between vitamin D receptor polymorphisms and GVHD. They found a significant association between GVHD and vitamin D receptor polymorphism.…”
Section: Discussionmentioning
confidence: 99%